Multifaceted phase ordering kinetics of an antiferromagnetic spin-1 condensate - Joanna Pietraszewicz (Nature Portfolio, 2021)
Abstract We study phase domain coarsening in the long time limit after a quench of magnetic field in a quasi one-dimensional spin-1 antiferromagnetic condensate. We observe that the growth of correlation length obeys scaling laws predicted by the two different models of phase ordering kinetics, namely the binary mixture and vector field. We derive regimes of clear realization for both of them. We demonstrate appearance of atypical scaling laws, which emerge in intermediate regions.